Optimization of process parameters to implement biomass gasifier for drying high moisture paddy in reversible flatbed dryer. (15th June 2022) - Wincy, W. Beno; Edwin, M.; Sekhar, S. Joseph
Abstract: Drying of high moisture paddy is one of the most attractive process for the possible use of rice husk (RH). To get maximum thermal energy from RH, thermochemical gasification technology can be implemented in drying. Therefore, this study investigates the possibility of implementing biomass gasifier to dry the soaked paddy in a Reversible Airflow Flatbed Dryer (RAFD). Response surface method is selected for the analysis. A designed set of experiments are used to find the Head Rice Yield (HRY), Overall System Efficiency (OSE), Specific Energy Consumption (SEC) and Specific Fuel Consumption (SFC). The important process parameters selected are Drying Air Temperature (DAT), Drying Air Velocity (DAV) and Bed Height (BH). The quadratic model of the central composite design methodology is selected to derive the relation between process and performance parameters. The results show that all the performance parameters are highly influenced by DAT followed by BH and DAV, and their optimal values are found as 81.99 °C, 8.97 cm and 0.05 m/s respectively. At this condition, the largest HRY and OSE are 62.4% and 59.198%, where the least Drying Time (DT), SEC and SFC are 5.349 h, 2.744 MJ/kg of water and 0.1022 kg rice husk/kg of paddy respectively. Graphical abstract: Image 1 Highlights: Biomass gasifier for drying high moisture paddy in a reversible flatbed dryer. Response surface methodology to optimize the process parameters of a paddy dryer. Hot-air of 81.99 °C and 0.05 m/s velocity dries parboiled paddy at high head rice yield. Producer gas used in the drying of parboiled paddy gives a head rice yield of 62.4%. The overall efficiency of a reversible flatbed dryer is 59.2% while biomass gasifier is used.